Produção e uso de jogo digital RPG na formação inicial de professores de biologia no contexto da aprendizagem baseada em jogos digitais: possibilidades e desafios - Amorim, Douglas Carvalho de (2017)
This study investigates what are the contributions of the production of a digital RPG game between undergraduates of Biological Sciences and students of the High School to the process of teaching and learning Biology in the context of learning based on digital games. The objective was to investigate how the digital RPG game production among undergraduates of Biological Sciences and high school students could contribute to the teaching and learning process of Biology by digital games based learning. The methodology involved an Action Research. The instruments of data collection used were focus groups, participant observation and annotations in logbooks. Content Analysis was used in data analysis. As results, from the creative process of the digital RPG game, we identified that the students presented critical sense regarding their experiences with RPG digital games and that they are not distant in generational terms when compared to the students of High School, bringing their experiences with games of this gender for the interpretation of their characters and properly selecting audiovisuals that contributed to the teaching process of Biology with the game. The contributions regarding the learning of the students of High School from the practice of creation of the digital RPG game were the high involvement of the same with the game mainly starting from the creation of the history of the game, characters and interpretation of roles by the subjects inserted in the school environment, besides presenting the ability to contextualize subjects related to Cytology in extraclass environments, such as the Study of the Environment.